(untitled) (Journal of International Crisis and Risk Communication Research, 2023)
The Philippines’ risk communication system relies on information dissemination, which disregards local capacity for managing risk. This research aimed to examine risk communication in Roxas City, an important economic center working on capacitation after damage by Supertyphoon Haiyan. Guided by Encoding–Decoding theory, the researcher interviewed government officers and facilitated discussions at coastal and inland communities. The researcher found that local government viewed communities as audiences who intuitively knew what to do with scientific information. The coastal community had indigenous knowledge but acted based on fear of sanctions. The inland community discussed information from media, which led to community decision-making. These findings imply that local governments should consider the role of social networks unique to different communities when planning risk communication and hazard response.